Mutational analysis of the Janus Kinase 2 gene in patients with polycythaemia vera, essential thrombocythaemia and primary myelofibrosis - Goodyear, Quintin Clive (University of the Free State, 2011)
All the cells of blood arise from two lineages, the myeloid and the lymphoid lineage. The various cells of blood perform vital functions in the body. These cell counts are closely regulated by regulatory pathways. Mutations within genes that encode for the proteins involved in these pathways can occur. These mutations can cause uncontrolled proliferation of the cells. Myeloproliferative neoplasms are malignancies where there is an uncontrolled increase in the formation of the myeloid cells. The four classical neoplasms are polycythaemia vera, essential thrombocythaemia, primary myelofibrosis and chronic myeloid leukaemia. A mutation (V617F) in the tyrosine kinase, Janus kinase 2, has been found to be the cause of at least three of the classical MPNs. The mutation lies in the domain of the protein that controls its tyrosine kinase activity. The tyrosine kinase thus is constitutively active and causes proliferation of the myeloid cells. The V617F mutation lies in exon 14 and more recently several mutations have been described in the neighbouring exons encoding for the regulatory domain of the gene. Very few studies have been done on the other exons of the JAK 2 gene. In the study it was attempted to screen 15 MPN patients for mutations in the JAK 2 gene. Two different cell populations (lymphocytes and granulocytes) of each patient were screened. It was found that the cell purity was not sufficient in the study and better separation techniques are required for future studies. Only the granulocytes were used for the remainder of the study. High resolution melting curve analysis was used to screen the patients for mutations, however the data did not correlate with the sequencing results and it was decided to proceed with sequencing of all the samples. Seven of the 25 exons of the JAK 2 gene were successfully sequenced. The remaining exons could not be screened due to time constraints and complications such as multiple amplicon formation. Two previously reported single nucleotide polymorphisms were found in exons 11 and 15 in two patients. The clinical significance thereof is uncertain however, the patient whom had the SNP in exon 15 was negative for the V617F mutation and had a MPN. In exon 14 the V617F mutation was identified and the prevalence thereof correlates to that reported in literature. A novel SNP was found in exon 13 of a PV patient negative for the V617F mutation and the significance thereof is also uncertain. Additionally a novel inverse duplication consisting of at least of exon 13 was also identified. No mutations were identified in exons 10, 12, 16 and 17 of the JAK 2 gene. This was, to our knowledge, the first report in South Africa that found the prevalence of the V617F mutation in MPN patients correlating to the prevalence reported in literature. A novel SNP was identified in exon 13 and further studies are needed on the possible effect thereof. The previously reported SNPs found in exons 11 and 15 might be the cause of the formation of a MPN, however further research is needed. A novel duplication variant was also identified and this might be a possible splice variant. The study showed that the region between exons 10 and 15 in the JAK 2 gene is a mutational hotspot and further studies are needed to elucidate the effect thereof.
Dissertation (M.Med.Sc. Haematology and Cell Biology))--University of the Free State, 2011
Keywords: Blood -- Diseases; Mycloproliferative disorders; Polycythemia vera; Molecular biology